The Quest For Continuous Improvement In A Malaysian Chinese Family Owned Company : An Interpretive Case Study - Cheah, Soo Jin (2011)
This thesis is the result of an in-depth case study of the quest for continuous quality improvement in a Malaysian Chinese family-owned company. The study reveals that Confucian philosophical values can be accounted for the company’s phenomenal growth when it was relatively small in size. The emphasis on trust, diligence, flexibility and frugality enabled the company to maintain a competitive edge in low transaction costs and flexible production policy. Even though, the company was granted the ISO 9000 certification, it still maintained the same management practices by decoupling the ISO quality management system from actual practice.